Characterization and Function of the ~70kDa Immunoreactive Species of Pannexin3 in Rhabdomyosarcomas - Gill, Kushal (Université d'Ottawa / University of Ottawa, 2015)
Rhabdomyosarcoma (RMS) is a skeletal muscle-derived tumour and is the most common soft tissue sarcoma of childhood. RMS tumours arise due to defects in differentiation, and as a result proliferate indefinitely. Pannexins consist of three members (pannexin1, 2, and 3) and are known to form single membrane channels. Reports have shown expression of pannexin3 (Panx3) as both the expected molecular weight species at ~43 kDa as well as a ~70 kDa immunoreactive species. While studies have begun to report on the function of the ~43 kDa form, the exact identity and function of the ~70 kDa immunoreactive species of Panx3 remains poorly understood. It has recently been reported that the ~70 kDa immunoreactive species of Panx3 is highly expressed in proliferative, non-differentiated human primary skeletal muscle myoblasts (HSMM), becoming drastically down regulated during differentiation. Indeed, knockdown of the ~70 kDa immunoreactive species of Panx3 inhibited proliferation without inducing differentiation in skeletal muscle myoblasts. We thus hypothesized that the ~70 kDa immunoreactive species of Panx3 would be upregulated in RMS supporting this proliferative phenotype. Here we now show that the ~70 kDa immunoreactive species of Panx3 is increased in RMS cell lines and tumours to a level similar to that seen in undifferentiated HSMM and fetal tissues, respectively. Further characterization of this species revealed that it is indeed a glycoprotein, an intrinsic characteristic of all pannexin members, it is recognized by two Panx3 antibodies targeting distinct epitopes, and it is reduced with Panx3 specific shRNA. Reduction of levels of the ~70 kDa immunoreactive species of Panx3 resulted in a significant decrease in proliferation of RMS cells without inducing differentiation. Taken together, these data suggest that the ~70 kDa immunoreactive species of Panx3 might be involved in keeping undifferentiated RMS cells in a proliferative state and that reduction of its levels or functions may be beneficial for RMS.
Keywords: Pannexin3; Rhabdomyosarcomas